From Faith to Empowerment: the Role of Majelis Taklim in Transforming Women's Lives - Muhammad Arif Syihabuddin; Fahida Jannatin Alfafa (MADINAH, 2026)
This study aims to find out how the learning process takes place at the Majelis Taklim As-Sholihah and its role in women's empowerment in Kedungrejo Village, Kedungadem District, Bojonegoro Regency. This research uses a qualitative method with a type of field research and a case study approach. Data was collected through observations, interviews with 11 informants, and documentation, then analyzed using the Miles Huberman model and tested for validity by triangulation. The results of the study show that the learning process in Majelis Taklim As-Sholihah takes place through various religious activities such as routine recitation, reciting the book, lectures, prayer readings, yasin and tahlil, and question and answer sessions. These activities help pilgrims in understanding Islamic teachings better and can be applied in daily life. Majelis Taklim As-Sholihah also plays a role in women's empowerment, which can be seen from the increase in religious understanding, self-confidence, role in the family, and women's activeness in social activities in society. Thus, Majelis Taklim As-Sholihah functions as a means of religious learning as well as a forum for women's empowerment in the social life of the community.